BAKTI SOSIAL KHITANAN MASSAL PADA MASYARAKAT DESA TAMALATEA KECAMATAN MANUJU KABUPATEN GOWA - Kusnadi Umar; Marwah Dwi Cahyani; Dwi Wulandari Rahman; Rismawati; Andi Munifah; Muh. Amirul Haq; Ario Prasetyo Rusman; Yasrif Wildan; Muh Yusril Ihza (Pangulu Abdi: Jurnal Pengabdian Kepada Masyarakat, 2023)
Starting from the intention of fellow students to share with others, the social service activity "Mass Circumcision" was held. This activity, which takes the form of a mass circumcision, is aimed at orphaned and underprivileged children. From a religious perspective, circumcision is mandatory and also from a medical perspective, it has many benefits, including maintaining physical cleanliness and reducing the risk of contracting disease. This activity is also a form of concern for underprivileged children in the Tamalatea Village area, Manuju District, Gowa Regency. The method used uses social intervention methods in approaching community members as a method for overcoming social and human resource (HR) problems in Tamalatea Village. How happy we are to be able to share with others, friendship between people can always be established and the final hope is that from this small concern, Allah Almighty will forever give a double reward and become an addition to the scale of our charity later.